Heparin in COVID-19 Patients Is Associated with Reduced In-Hospital Mortality: The Multicenter Italian CORIST Study - Di Castelnuovo, Augusto; Costanzo, Simona; Antinori, Andrea; Berselli, Nausicaa; Blandi, Lorenzo; Bonaccio, Marialaura; Cauda, Roberto; Guaraldi, Giovanni; Menicanti, Lorenzo; Mennuni, Marco; Parruti, Giustino; Patti, Giuseppe; Santilli, Francesca; Signorelli, Carlo; Vergori, Alessandra; Abete, Pasquale; Ageno, Walter; Agodi, Antonella; Agostoni, Piergiuseppe; Aiello, Luca; Al Moghazi, Samir; Arboretti, Rosa; Astuto, Marinella; Aucella, Filippo; Barbieri, Greta; Bartoloni, Alessandro; Bonfanti, Paolo; Cacciatore, Francesco; Caiano, Lucia; Carrozzi, Laura; Cascio, Antonio; Ciccullo, Arturo; Cingolani, Antonella; Cipollone, Francesco; Colomba, Claudia; Colombo, Crizia; Crosta, Francesca; Danzi, Gian Battista; D'Ardes, Damiano; de Gaetano Donati, Katleen; Di Gennaro, Francesco; Di Tano, Giuseppe; D'Offizi, Gianpiero; Fantoni, Massimo; Fusco, Francesco Maria; Gentile, Ivan; Gianfagna, Francesco; Grandone, Elvira; Graziani, Emauele; Grisafi, Leonardo; Guarnieri, Gabriella; Larizza, Giovanni; Leone, Armando; Maccagni, Gloria; Madaro, Ferruccio; Maitan, Stefano; Mancarella, Sandro; Mapelli, Massimo; Maragna, Riccardo; Marcucci, Rossella; Maresca, Giulio; Marongiu, Silvia; Marotta, Claudia; Marra, Lorenzo; Mastroianni, Franco; Mazzitelli, Maria; Mengozzi, Alessandro; Menichetti, Francesco; Meschiari, Marianna; Milic, Jovana; Minutolo, Filippo; Molena, Beatrice; Montineri, Arturo; Mussini, Cristina; Musso, Maria; Niola, Daniela; Odone, Anna; Olivieri, Marco; Palimodde, Antonella; Parisi, Roberta; Pasi, Emanuela; Pesavento, Raffaele; Petri, Francesco; Pinchera, Biagio; Poletti, Venerino; Ravaglia, Claudia; Rognoni, Andrea; Rossato, Marco; Rossi, Marianna; Sangiovanni, Vincenzo; Sanrocco, Carlo; Scorzolini, Laura; Sgariglia, Raffaella; Simeone, Paola Giustina; Taddei, Eleonora; Torti, Carlo; Vettor, Roberto; Vianello, Andrea; Vinceti, Marco; Virano, Alexandra; Vocciante, Laura; De Caterina, Raffaele; Iacoviello, Licia (Thrombosis and Haemostasis, 2021)
Introduction A hypercoagulable condition was described in patients with coronavirus disease 2019 (COVID-19) and proposed as a possible pathogenic mechanism contributing to disease progression and lethality.Aim We evaluated if in-hospital administration of heparin improved survival in a large cohort of Italian COVID-19 patients.Methods In a retrospective observational study, 2,574 unselected patients hospitalized in 30 clinical centers in Italy from February 19, 2020 to June 5, 2020 with laboratory-confirmed severe acute respiratory syndrome coronavirus-2 infection were analyzed. The primary endpoint in a time-to event analysis was in-hospital death, comparing patients who received heparin (low-molecular-weight heparin [LMWH] or unfractionated heparin [UFH]) with patients who did not. We used multivariable Cox proportional-hazards regression models with inverse probability for treatment weighting by propensity scores.Results Out of 2,574 COVID-19 patients, 70.1% received heparin. LMWH was largely the most used formulation (99.5%). Death rates for patients receiving heparin or not were 7.4 and 14.0 per 1,000 person-days, respectively. After adjustment for propensity scores, we found a 40% lower risk of death in patients receiving heparin (hazard ratio = 0.60; 95% confidence interval: 0.49–0.74; E-value = 2.04). This association was particularly evident in patients with a higher severity of disease or strong coagulation activation.Conclusion In-hospital heparin treatment was associated with a lower mortality, particularly in severely ill COVID-19 patients and in those with strong coagulation activation. The results from randomized clinical trials are eagerly awaited to provide clear-cut recommendations.
Keywords: COVID-19; coronavirus; heparin; coagulation activation; treatments; mortality